2015
DOI: 10.1016/j.biochi.2014.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Comparative biochemical analysis of three members of the Schistosoma mansoni TAL family: Differences in ion and drug binding properties

Abstract: The tegumental allergen-like (TAL) proteins from Schistosoma mansoni are part of a family of calcium binding proteins found only in parasitic flatworms. These proteins have attracted interest as potential drug or vaccine targets, yet comparatively little is known about their biochemistry. Here, we compared the biochemical properties of three members of this family: SmTAL1 (Sm22.6), SmTAL2 (Sm21.7) and SmTAL3 (Sm20.8). Molecular modelling suggested that, despite similarities in domain organisation, there are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(67 citation statements)
references
References 67 publications
5
62
0
Order By: Relevance
“…Both domains of the protein are involved in dimerization: the EF-hand domain and the DLC-like domain can both be cross-linked under similar conditions to the full length protein. This contrasts with FhCaBP3 and FhCaBP4 which homodimerize in a calcium sensitive manner, but is similar to the S. mansoni proteins SmTAL1 and SmTAL2 which form calcium-insensitive homodimers (Orr et al 2012;Banford et al 2013;Thomas et al 2015). However, cross-linking of the DLC-like domain was not greatly affected by the presence or absence of calcium or manganese ions (Fig.…”
Section: Dimerization Of Fhcabp2 and Its Domainsmentioning
confidence: 81%
See 2 more Smart Citations
“…Both domains of the protein are involved in dimerization: the EF-hand domain and the DLC-like domain can both be cross-linked under similar conditions to the full length protein. This contrasts with FhCaBP3 and FhCaBP4 which homodimerize in a calcium sensitive manner, but is similar to the S. mansoni proteins SmTAL1 and SmTAL2 which form calcium-insensitive homodimers (Orr et al 2012;Banford et al 2013;Thomas et al 2015). However, cross-linking of the DLC-like domain was not greatly affected by the presence or absence of calcium or manganese ions (Fig.…”
Section: Dimerization Of Fhcabp2 and Its Domainsmentioning
confidence: 81%
“…The protein also interacts with manganese ions, a common feature with FhCaBP3 and FhCaBP4 and some members of the S. mansoni TAL family proteins (Orr et al 2012;Banford et al 2013;Thomas et al 2015). The protein also interacts with manganese ions, a common feature with FhCaBP3 and FhCaBP4 and some members of the S. mansoni TAL family proteins (Orr et al 2012;Banford et al 2013;Thomas et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This region can decrease the quality of the overall model, as it requires additional simulation time, and it interferes with the structural clustering process [25]. These regions have been predicted representing tegumental protein linkers because they lack secondary structure in Schistosoma mansoni [26] and Fasciola hepatica [27]. To address this issue, we split the whole sequence into two domains, domain 1 (aa1–74) and domain 2 (aa75–175), based on the disordered region rather than removing the region.…”
Section: Resultsmentioning
confidence: 99%
“…DLC-containing proteins can form homodimers through hydrogen bonds, backbone-side chain electrostatic interactions and van der Waals contacts between side chains [43]. Previous studies have indicated that the homodimeric DLCs in S. mansoni [26] and F. hepatica [27] were composed of two asymmetric monomers through β-sheet interactions. The homodimer of CsTegu20.6 was constructed using GalaxyGemini [44] with only the C chain of DLC1 (PDB ID: 4DS1_C), although the fifth β-strand (indicated with a dotted circles) as a monomeric counterpart was missed in the predicted structure [45] (Figure 5C).…”
Section: Resultsmentioning
confidence: 99%